Satellite Images Fusion Using Modified PCA Substitution Method - Abduljabbar, Hameed Majeed (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this paper, a new tunable approach for fusion the satellite images that fall in different electromagnetic wave ranges is presented, which gives us the ability to make one of the images features little superior on the other without reducing the general resultant image fusion quality, this approach is based on the principal component analysis (PCA) fusion method. A comparison made is between the results of the proposed approach and two fusion methods (they are: the PCA fusion method and the projection of eigenvectors on the bands fusion method), and the comparison results show the validity of this new method.